2023
DOI: 10.1097/pas.0000000000002108
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumor of the Pancreas

Abstract: Solitary fibrous tumor (SFT) has been increasingly reported in various anatomic sites. However, it is still extremely rare in the pancreas. Herein, we present the first series of primary pancreatic SFTs. Nine cases of primary pancreatic SFTs were analyzed. The mean age was 60 years (36 to 76 y) with no sex predilection. Six tumors were in the head, 3 were in the tail. On imaging studies, tumors were described as a hypervascular mass, 2 revealed cystic areas, and 3 were favored to be neuroendocrine tumors. On b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…
This article describes the analysis of 9 cases and a literature review of solitary fibrous tumors (SFTs) of the pancreas. 1 The study showed that STAT6 is a useful marker for diagnosing SFTs in pancreatic tumors. Nuclear STAT6 expression was observed in 7 of the 8 examined SFTs.
…”
mentioning
confidence: 94%
“…
This article describes the analysis of 9 cases and a literature review of solitary fibrous tumors (SFTs) of the pancreas. 1 The study showed that STAT6 is a useful marker for diagnosing SFTs in pancreatic tumors. Nuclear STAT6 expression was observed in 7 of the 8 examined SFTs.
…”
mentioning
confidence: 94%